THE MEANING OF DEATH IN A PSYCHOSOPHYSTIC PERSPECTIVE - Rohmatullah, Yuminah; Arif, Basyir (ILMU USHULUDDIN, 2023)
The study employs a dual approach, combining psychological analysis with Sufi teachings to comprehend the multifaceted nature of death. Methodologically, it synthesizes insights from psychological theories on emotional detachment and the human perception of mortality. This is juxtaposed with the Sufi perspective, derived from extensive literature, teachings, and interpretations of Sufi scholars and texts. The psychological aspect delves into the notion of psychological death, exploring how individuals, while physically alive, can experience emotional numbness, disconnect, and insensitivity to their surroundings. This exploration incorporates established psychological frameworks and case studies that illustrate these states. Simultaneously, the Sufistic approach interprets death as an inevitable certainty, emphasizing the spiritual separation between the body and the eternal soul. This perspective draws upon Sufi texts, traditions, and philosophies that emphasize the eternal nature of the soul and the transformative aspect of death. The study synthesizes these perspectives, aiming to provide a comprehensive understanding of death. It examines how the psychological and Sufi viewpoints converge and diverge, shedding light on the multifaceted meanings and implications of death within the human experience. Through this methodological fusion, the study endeavors to offer a nuanced perspective on death that encompasses both psychological and spiritual dimensions.